Development of the Brinell Method: For Macro-, Micro- and Nano Ranges : monograph - Moshchenok, Vasyl; Moshchenok, Vasyl V.; Moshchenok, Mykhailo (Харківський національний автомобільно-дорожній університет, 2025)
The monograph “Development of the Brinell Method for Macro-, Micro-, and Nano Ranges” presents a comprehensive scientific and practical modernization of the classical Brinell hardness testing method. It explores theoretical foundations, international standards, and experimental techniques for measuring hardness at macro, micro, and nano scales using both recovered and unrecovered indentation. The work introduces new classifications of hardness (surface, projection, volume), methods for evaluating material properties with spherical-conical indenters, and practical guidelines for adapting traditional equipment to modern precision tasks. This book is a valuable resource for researchers, engineers, and educators in materials science and mechanical engineering.
Keywords: hardness testing methods for metals and alloys; determination of hardness according to brinell; new approaches to metal hardness testing; textbook for technical university students; indentation size effect; advanced nanotechnology for nanoindentation; indenters for hardness testers and nanotechnology